2012
DOI: 10.1021/jo2023262
|View full text |Cite
|
Sign up to set email alerts
|

Selective Palladium-Catalyzed C–F Activation/Carbon–Carbon Bond Formation of Polyfluoroaryl Oxazolines

Abstract: A selective palladium-catalyzed Suzuki-Miyaura coupling reaction of polyfluorophenyl oxazolines through ortho C-F activation is described. It was found that reactions with DPPF as the ligand occurred much faster than those with other ligands. A variety of arylboronic acids including challenging functionalized arylboronic acids such as enolizable ketones, aldehyde, cyano, ester, and trifluoromethyl groups were tolerated with the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(20 citation statements)
references
References 39 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…Further investigation revealed that only trace amount of desired product 3 e was observed under catalytic reaction conditions (Scheme 2 b). [20] As shown in Scheme 3, compounds 7 and 8 can be easily prepared by palladium-catalyzed cross-coupling of 1 or 5 with various aryl and alkenyl species including boronic acids, borates and silanes. As to the formation of II-2, we reasoned that when [{PdCl(C 3 H 5 )} 2 ] was treated with Et 3 SiH and dppe, besides the formation of Pd 0 species, Et 3 SiCl was also generated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation revealed that only trace amount of desired product 3 e was observed under catalytic reaction conditions (Scheme 2 b). [20] As shown in Scheme 3, compounds 7 and 8 can be easily prepared by palladium-catalyzed cross-coupling of 1 or 5 with various aryl and alkenyl species including boronic acids, borates and silanes. As to the formation of II-2, we reasoned that when [{PdCl(C 3 H 5 )} 2 ] was treated with Et 3 SiH and dppe, besides the formation of Pd 0 species, Et 3 SiCl was also generated.…”
Section: Methodsmentioning
confidence: 99%
“…To illustrate the potential applications of this method, the construction of C À C bond by C À F bond activation has also been examined. [20] As shown in Scheme 3, compounds 7 and 8 can be easily prepared by palladium-catalyzed cross-coupling of 1 or 5 with various aryl and alkenyl species including boronic acids, borates and silanes.…”
Section: Methodsmentioning
confidence: 99%
“…75) [132]. The transformation was tolerant to a large selection of functional groups including cyano, ester, ketones, aldehydes, and trifluoromethyl groups.…”
Section: ð72; 73þ Catalytic Examplesmentioning
confidence: 99%
“…In this case the same trends as those mentioned for the nitro derivatives are observed: Selective functionalization of the ortho fluorine and lower reactivity as the number of fluorine atoms in the ring decrease. 235 The same authors reported an interesting coupling that involves a C-H activation of the non-fluorinated partner (Scheme 76, L = diphosphine). 236 In this case a 2-pyridinyl group as directing group was more effective than the oxazoline used before.…”
Section: Scheme 74mentioning
confidence: 99%